Evolution of the Sibişel Shear Zone (South Carpathians): A study of its type locality near Răşinari (Romania) and tectonic implications. Issue 9 (26th September 2016) - Ducea, Mihai N.; Negulescu, Elena; Profeta, Lucia; Săbău, Gavril; Jianu, Denisa; Petrescu, Lucian; Hoffman, Derek
Abstract: The Sibişel Shear Zone is a 1–3 km wide, ductile shear zone located in the South Carpathian Mountains, Romania. In the Rășinari area, the ductile shear zone juxtaposes amphibolite facies rocks of the Lotru Metamorphic Suite against greenschist facies rocks of the Râuşorul Cisnădioarei Formation. The first represents the eroded remnants of Peri‐Gondwanan arcs formed between the Neoproterozoic‐Silurian (650–430 Ma), regionally metamorphosed to amphibolite facies during the Variscan orogeny (350–320 Ma). The second is composed of metasedimentary and metavolcanic Neoproterozoic‐Ordovician (700–497 Ma) assemblages of mafic to intermediate bulk composition also resembling an island arc metamorphosed during the Ordovician (prior to 463 Ma). Between these lie the epidote amphibolite facies mylonitic and ultramylonitic rocks of the Sibișel Formation, a tectonic mélange dominated by mafic actinolite schists attenuated into a high strain ductile shear zone. Mineral Rb‐Sr isochrons document the time of juxtaposition of the three domains during the Permian to Early Triassic ( 290–240 Ma). Ductile shear sense indicators suggest a right lateral transpressive mechanism of juxtaposition; the Sibişel shear zone is a remnant Permo‐Triassic suture between two Early Paleozoic Gondwanan terranes. A zircon and apatite U‐Th/He age transect across the shear zone yields Alpine ages (54–90 Ma apatite and 98–122 Ma zircon); these data demonstrate that the exposed rocks were not subjected to Alpine ductile deformation. Our results have significant implications for the assembly of Gondwanan terranes and their docking to Baltica during Pangea's formation. Arc terranes free of Variscan metamorphism existed until the Early Triassic, emphasizing the complex tectonics of terrane amalgamation during the closure of Paleotethys. Key Points: Major ductile shear zone delimitates two arc terranes in the Carpathians Terrane accretion extended until well after the Variscan (Carboniferous age) mega collision in eastern Europe The shear zone is a paleosuture